2020
DOI: 10.1177/0027432120950812
|View full text |Cite
|
Sign up to set email alerts
|

Developing Self-Efficacy to Improve Music Achievement

Abstract: Albert Bandura identified self-efficacy as the dominant self-perception shaping action, effort, and achievement. In music education, researchers have identified a positive relationship between self-efficacy and achievement, but how can music educators develop self-efficacy to improve achievement? This article offers a description of self-efficacy and provides practical strategies to promote its development in music education. These strategies can be applied in any music learning environment so that music educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…As such, the experience of musicing in the process of adaptation to the impairment played a central role, giving them the sense of autonomy through independent activity, satisfaction through accomplishment, and social communication or empathy, thereby ultimately leading to growth (Lee, 2015). This may be attributed to the process of creating music as a group having a significant influence on increasing not only the personal experience of accomplishment but also self-efficacy (McPherson and McCormick, 2006;Hendricks, 2016;Zelenak, 2020). Hence, music is likely to have reinvigorated individuals with AVI to live on, by letting them actively apply their remaining senses and attain a sense of immediate reward (Rostohar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the experience of musicing in the process of adaptation to the impairment played a central role, giving them the sense of autonomy through independent activity, satisfaction through accomplishment, and social communication or empathy, thereby ultimately leading to growth (Lee, 2015). This may be attributed to the process of creating music as a group having a significant influence on increasing not only the personal experience of accomplishment but also self-efficacy (McPherson and McCormick, 2006;Hendricks, 2016;Zelenak, 2020). Hence, music is likely to have reinvigorated individuals with AVI to live on, by letting them actively apply their remaining senses and attain a sense of immediate reward (Rostohar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A scale for measuring self-efficacy was adapted from Zelenak’s (2020) Music Performance Self-Efficacy Scale (MPSES), which was supplemented by four items to differentiate measurement in performance situations, such as competitions, in class, performance of instrumental solo, and solo performances (27 items in total). Both scales were translated into the German language and rechecked for adequacy by a native speaker in both languages.…”
Section: Methodsmentioning
confidence: 99%
“…Research has identified four main motivational topics in music: satisfying personal needs, developing and maintaining a positive musical identity, acquiring effective approaches to learning music, and having a supportive environment (Hallam, 2013; Hallam et al, 2016; Schmidt, 2005). Recently, Zarza-Alzugaray et al (2020) added musical practice self-efficacy to this list of motivational issues, that is, the confidence in one’s capabilities of being able to perform successfully is impacted by four factors: mastery experiences, vicarious experiences, verbal/social persuasion, and physiological state (Zelenak, 2020). Nielsen (2004) showed that music students with more self-efficacy used better the learning material.…”
Section: The Value Of Motivation and Self-efficacy For Deliberate Pra...mentioning
confidence: 99%
“…The way in which singers perceive their own voices, themselves, and their learning experiences are intricately connected (Abitbol, 2016; O’Bryan, 2015). Self-efficacy is likewise tied to perception of oneself (Bandura, 1993), and plays a major role in determining student success in music (Fisher, 2014; Zelenak, 2020; Zimmerman, 2000). The FAVC is not solely measured in objective physical and acoustic voice characteristics, but also in the perceptual experience and individualistic nature of these changes (Sweet, 2019).…”
Section: The Literaturementioning
confidence: 99%
“…In the light of such nuanced and individual changes, a question here arises as to how voice teachers can help students to identify the normal characteristics of FAVC in their own voices and develop a view of such that facilitates continued development of singing skills during adolescence with healthy self-efficacy, self-image, and resilience. Within the Aotearoa New Zealand secondary school context, there is a highly competitive group-singing tradition-heightened by some teachers' unrelenting subscription to local and national singing competitions-that may hinder self-aware and compassionate voice teaching and learning, to the extent that students stop singing all together (Baker, 2018;Fisher, 2014;Hendricks, 2014;Zelenak, 2020;Zimmerman, 2000). As a voice teacher develops their own pedagogical values, the need for wholistic and emotionally-integrated approaches to teaching and learning become more and more apparent (O'Bryan, 2014(O'Bryan, , 2015Rakena & Bresler, 2016).…”
Section: Voice Change Experiences and Perceptionsmentioning
confidence: 99%